Effects of a Universal Classroom Management Intervention on Middle School Students With or At Risk of Behavior Problems. (January 2021) - Sinclair, James; Herman, Keith C.; Reinke, Wendy M.; Dong, Nianbo; Stormont, Melissa
Universal interventions implemented in schools have the potential to impact large numbers of students on a multitude of behavioral and academic outcomes. In the context of a large group randomized controlled trial, the current study examined whether teacher-perceived student need for behavior support plans at baseline moderated the effects of a middle school universal classroom management training program, CHAMPS, which stands for Conversation, Help, Activity, Movement, Participation, and Success, on student outcomes. We hypothesized that students in CHAMPS classrooms who were identified by teachers at baseline as needing behavior support plans would have greater end-of-year improvements on behavior and academic outcomes relative to comparable youth in non-CHAMPS classrooms. Results indicated baseline teacher-perceived student behavior support need moderated some intervention outcomes; in particular, youth at risk in CHAMPS classrooms demonstrated improvements in concentration problems ( b = –.19) and communication arts outcomes ( b = .13) compared with youth at risk in control group classrooms. Implications of these findings and future research are discussed.